European Working Time Directive and doctors’ health: a systematic review of the available epidemiological evidence - Consol Serra; Evangelia Demou; Ewan B Macdonald; Sergio Vargas-Prada; Maria Cruz Rodriguez-Jareño; Kaveh A Sanati; Alenka Škerjanc; Pedro G Reis; Ritva Helimäki-Aro (BMJ Open)
Objective To summarise the available scientific evidence on the health effects of exposure to working beyond the limit number of hours established by the European Working Time Directive (EWTD) on physicians.Design A systematic literature search was conducted in PubMed and EMBASE. Study selection, quality appraisal and data extraction were carried out by independent pairs of researchers using pre-established criteria.Setting Physicians of any medical, surgical or community specialty, working in any possible setting (hospitals, primary healthcare, etc), as well as trainees, residents, junior house officers or postgraduate interns, were included.Participants The total number of participants was 14 338.Primary and secondary outcome measures Health effects classified under the International Classification of Diseases (ICD-10).Results Over 3000 citations and 110 full articles were reviewed. From these, 11 studies of high or intermediate quality carried out in North America, Europe and Japan met the inclusion criteria. Six studies included medical residents, junior doctors or house officers and the five others included medical specialists or consultants, medical, dental, and general practitioners and hospital physicians. Evidence of an association was found between percutaneous injuries and road traffic accidents with extended long working hours (LWH)/days or very LWH/weeks. The evidence was insufficient for mood disorders and general health. No studies on other health outcomes were identified.Conclusions LWH could increase the risk of percutaneous injuries and road traffic accidents, and possibly other incidents at work through the same pathway. While associations are clear, the existing evidence does not allow for an established causal or ‘dose–response’ relationship between LWH and incidents at work, or for a threshold number of extended hours above which there is a significantly higher risk and the hours physicians could work and remain safe and healthy. Policymakers should consider safety issues when working on relaxing EWTD for doctors.